2018
DOI: 10.1007/s40333-018-0014-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial activity and community structure as affected by exposure to chloride and chloride-sulfate salts

Abstract: Mixed or chloride salty ions dominate in saline soils, and exert wide-ranging adversely affect on soil biological processes and soil functions. The objectives of this study were to (1) explore the impacts of mixed (0, 3, 6, 10, 20 and 40 g Cl-/SO 4 2-salt/kg dry soil) and chloride (0, 1.5, 3, 5, 8 and 15 g Clsalt/kg dry soil) salts on soil enzyme activities, soil physiological functional (Biolog) profiles and microbial community structure by using soil enzymatic, Biolog-Eco microplates as well as denaturing gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Recent studies have reported the characteristics of microbial communities in forest and farmland ecosystems (Teurlincx et al, 2018;Liang et al, 2019;Shao et al, 2019;Liu et al, 2021) and research on microbial communities in saline-alkali lands should be paid more attention. Salinity is one of the main factors affecting soil microbial diversity and composition in saline-alkali areas (Zhang et al, 2018;Yang and Sun, 2020;Zhao et al, 2020). The vegetation in saline-alkali areas is dominated by halophytes, which have an important impact on soil microbial communities (Cao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported the characteristics of microbial communities in forest and farmland ecosystems (Teurlincx et al, 2018;Liang et al, 2019;Shao et al, 2019;Liu et al, 2021) and research on microbial communities in saline-alkali lands should be paid more attention. Salinity is one of the main factors affecting soil microbial diversity and composition in saline-alkali areas (Zhang et al, 2018;Yang and Sun, 2020;Zhao et al, 2020). The vegetation in saline-alkali areas is dominated by halophytes, which have an important impact on soil microbial communities (Cao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the initial microbial communities we might obtain might differ but will allow for an investigation of the generalizability of salt specificity on microbial community structures. We hypothesized that salt amendments differing in their ionic composition but at concentrations resulting in comparable natural freshwater‐specific conductance will have significant, albeit differential, effects on community α‐diversity (H1) and functional potential (H2) regardless of the state of origin (DeVilbiss et al, 2022; Zhang et al, 2018). We anticipated ‘core’ orders of each state to persist despite salt amendments, albeit at varying relative abundances, as these orders are generally associated with maintaining the basal functionality of the community (Custer et al, 2023; Shade & Handelsman, 2012).…”
Section: Introductionmentioning
confidence: 99%